Research on Dynamic Modeling and Application of Kinetic Contact Interface in Machine Tool - Dan Xu; Zhixin Feng (Shock and Vibration)
A method is presented which is a kind of combining theoretic analysis and experiment to obtain the equivalent dynamic parameters of linear guideway through four steps in detail. From statics analysis, vibration model analysis, dynamic experiment, and parameter identification, the dynamic modeling of linear guideway is synthetically studied. Based on contact mechanics and elastic mechanics, the mathematic vibration model and the expressions of basic mode frequency are deduced. Then, equivalent stiffness and damping of guideway are obtained in virtue of single-freedom-degree mode fitting method. Moreover, the investigation above is applied in a certain gantry-type machining center; and through comparing with simulation model and experiment results, both availability and correctness are validated.